Three Artistic Hypotheses about Time and Chronology, and Their Consequences for Understanding History and the Subject, Including the Relationship between Them (Even if Their Status Remains Questionable) - Falkowski, Mateusz (Sensus Historiae, 2025)
In this text, I attempt to consider the problem of the relationship between history and the subject in the field of art, taking into account the customary analysis of artistic works in a historical context. Drawing on the reflections of Eliot, Borges, and Gould, I point out the limitations of such analysis. Contrary to the traditional approach, a work of art is created on the basis of virtual elements that can enter into relationships with many contexts. This requires a different approach to the temporality of art itself, which is no longer characterized by unidirectionality.